1997
DOI: 10.1021/jf970216t
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Volatile Mono- and Sesquiterpenoids in Highland and Lowland Plant Species as Possible Precursors for Flavor Compounds in Milk and Dairy Products

Abstract: This paper examines the distribution of mono- and sesquiterpene secondary metabolites in 47 plants present in grazing areas from which cheeses are produced. In total, 54 terpenoid volatiles, derived from both highland and lowland plants, were obtained by a gaseous purge-and-trap system without the use of organic solvents and then identified by automated GC/MSD-FID analysis using mass spectral libraries, retention indices, and data acquired by the authors with authentic substances. Single ion monitoring proved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 19 publications
5
131
0
10
Order By: Relevance
“…The terpenes and hydrocarbons identified are probably because of the sheep feeding (Dumont & Adda, 1979). Some authors demonstrated that benzyl compounds, including toluene, come from the degradation of carotene in milk (Johnson, Nursten, & Self, 1969), whereas terpenes come from the pasture diet of the animals (Mariaca et al, 1997). Particularly, Figura 1.…”
Section: Resultsmentioning
confidence: 99%
“…The terpenes and hydrocarbons identified are probably because of the sheep feeding (Dumont & Adda, 1979). Some authors demonstrated that benzyl compounds, including toluene, come from the degradation of carotene in milk (Johnson, Nursten, & Self, 1969), whereas terpenes come from the pasture diet of the animals (Mariaca et al, 1997). Particularly, Figura 1.…”
Section: Resultsmentioning
confidence: 99%
“…These plant-specific molecules, when concentrated, have recognised aromatic properties. They abound in certain species, dicotyledons in particular [26,74]. These molecules very rapidly pass into the milk [124] and are found in cheese in a much greater quantity when the animals are fed dicotyledon-rich natural grass forage than when they are fed concentratebased rations [85], or monospecific forage [13,15,17,123].…”
Section: Direct Transfermentioning
confidence: 99%
“…Cheeses M and VX, which were the most rich in terpenes, were made from the most terpene-rich milks [15]. According to Bugaud et al [15] and Viallon et al [40], the terpene composition of milk depends on that of the forage consumed, which in turn depends on the botanical composition of the forage [14,33]. Most notably, M and VX pastures where dicotyledons -in particular umbelliferae, composites and plantaginaceae -were predominant, were the most terpene-rich, both in terms of diversity and quantity [14].…”
Section: Volatile Compounds In Cheesementioning
confidence: 99%